Formulation optimization, in vitro and in vivo evaluation of niosomal nanocarriers for enhanced topical delivery of cetirizine - Mohammed F. Aldawsari; El-Sayed Khafagy; Ehssan H. Moglad; Amr Selim Abu Lila (Elsevier, 2023)
Cetirizine hydrochloride (CTZ), a second-generation anti-histaminic drug, has been recently explored for its effectiveness in the treatment of alopecia. Niosomes are surfactant-based nanovesicular systems that have promising applications in both topical and transdermal drug delivery. The aim of this study was to design topical CTZ niosomes for management of alopecia. Thin film hydration technique was implemented for the fabrication of CTZ niosomes. The niosomes were examined for vesicle size, surface charge, and entrapment efficiency. The optimized niosomal formulation was incorporated into a hydrogel base (HPMC) and explored for physical characteristics, ex vivo permeation, and in vivo dermato-kinetic study. The optimized CTZ-loaded niosomal formulation showed an average size of 403.4 ± 15.6 nm, zeta potential of − 12.9 ± 1.7 mV, and entrapment efficiency percentage of 52.8 ± 1.9%. Compared to plain drug solution, entrapment of CTZ within niosomes significantly prolonged in vitro drug release up to 12 h. Most importantly, ex-vivo skin deposition studies and in vivo dermato-kinetic studies verified superior skin deposition/retention of CTZ from CTZ-loaded niosomal gels, compared to plain CTZ gel. CTZ-loaded niosomal gel permitted higher drug deposition percentage (19.2 ± 1.9%) and skin retention (AUC0-10h 1124.5 ± 87.9 μg/mL.h) of CTZ, compared to 7.52 ± 0.7% and 646.2 ± 44.6 μg/mL.h for plain CTZ gel, respectively. Collectively, niosomes might represent a promising carrier for the cutaneous delivery of cetirizine for the topical management of alopecia.